(untitled) (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2025)
This paper gives a computational fluid dynamics (CFD) of the flow of an incompressible fluid through a 90deg pipe bend on the open-source SimScale platform. The flow of curved pipes is typified by the redistribution of velocity, development of a secondary flow and pressure losses so the primary goal is to determine the magnitude of the pressure losses and study the behaviour of velocity and the behaviour of separation as a function of Reynolds number and bend curvature. The parametric study of the elbow geometries is followed with variable curvature ratios (rc/D) and flow conditions (laminar and turbulent) on the geometries. Structured meshes in which the near-wall refinement has been used and steady Reynolds-averaged Navier-Stokes (RANS) turbulence models which are the standard k-e model and the SST k-o model are used to perform simulations with chosen transient cases to capture unsteady separation. The analysis has been conducted on pressure loss coefficients and velocity profiles, pressure contours, and the second flow patterns. The findings indicate the great effect of bend geometry and flow regime on flow organization and energy losses. The paper draws attention to the originality of utilizing an open-access CFD platform, which offers a reproducible numerical model, which can be used in teaching engineering and in initial design and subsequent experimental support.